Nitrogen removal from digested slurries using a simplified ammonia stripping technique. (November 2017) - Provolo, Giorgio; Perazzolo, Francesca; Mattachini, Gabriele; Finzi, Alberto; Naldi, Ezio; Riva, Elisabetta
Graphical abstract: Highlights: A novel application of N stripping for anaerobic digestates was studied. The studied process combines mixing, pH adjustment and continuous air flow. High ammonia removal efficiency (87%) was achieved at pH 9 and 40  ° C. Acceptable ammonia removal efficiency (69%) was achieved without pH adjustment. Technique is a viable option for farms especially combined with biogas plants. Abstract: This study assessed a novel technique for removing nitrogen from digested organic waste based on a slow release of ammonia that was promoted by continuous mixing of the digestate and delivering a continuous air stream across the surface of the liquid. Three 10-day experiments were conducted using two 50-L reactors. In the first two, nitrogen removal efficiencies were evaluated from identical digestates maintained at different temperatures (30 °C and 40 °C). At the start of the first experiment, the digestates were adjusted to pH 9 using sodium hydroxide, while in the second experiment pH was not adjusted. The highest ammonia removal efficiency (87%) was obtained at 40 °C with pH adjustment. However at 40 °C without pH adjustment, removal efficiencies of 69% for ammonia and 47% for total nitrogen were obtained. In the third experiment two different digestates were tested at 50 °C without pH adjustment. Although the initial chemical characteristics of the digestates were different in this experiment, the ammonia removal efficiencies were very similar (approximately 85%). Despite ammonia removal, the pH increased in all experiments, most likely due to carbon dioxide stripping that was promoted by temperature and mixing. The technique proved to be suitable for removing nitrogen following anaerobic digestion of livestock manure because effective removal was obtained at natural pH (≈8) and 40 °C, common operating conditions at typical biogas plants that process manure. Furthermore, the electrical energy requirement to operate the process is limited (estimated to be 3.8 kW h m −3  digestate). Further improvements may increase the efficiency and reduce the processing time of this treatment technique. Even without these advances slow-rate air stripping of ammonia is a viable option for reducing the environmental impact associated with animal manure management.